Pengembangan Kompetensi Profesional Guru Melalui Strategi Penulisan Karya Ilmiah: Pengabdian - Baharuddin; Muthi, Ibnu; Haryono, Pauzan; Rubai Misbahul Alam, Dede; Yuli Sugiarti, Diyah; Muntaha; Apriliantoni; Annuri; Darwis; Eriyatuzzahro; Khumaidi, Ahmad; Paradiyawan; Sumodiharjo, Bambang; Dindin; Ulfa, Maria (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity aims to improve the ability of teachers at the As-Syifa Al-Khaeriyah Subang Foundation to write quality scientific papers that are worthy of publication. This activity was carried out in collaboration with the Unisma Bekasi Graduate School as a form of academic contribution in supporting teacher professionalism through strengthening academic literacy. The method of implementing the activity consisted of a pre-test to measure initial understanding, interactive training that included material on the nature of scientific papers, writing structures, article preparation techniques, and the selection of appropriate journals, and ended with writing practice and a clinic for the revision of participants' works. This activity was held for a full day on April 13, 2025, with a total of 50 teachers participating. The results of the activity showed a significant increase in the aspects of knowledge, technical skills, and positive attitude of teachers towards scientific paper writing activities. Post-test evaluation showed an increase in the average comprehension score of participants compared to pre-test. In addition, participants also showed enthusiasm and commitment to developing a writing culture in their respective school environments.